Verzár Frigyes élettanprofesszor, a Debreceni M. Kir. Tisza István Tudományegyetem 1927/28. tanévi rector magnificusa - Zs. Nagy, Imre (Gerundium, 2016)
Frigyes Verzár, Professor of Physiology and Rector Magnificus of István Tisza Hungarian Royal University in Debrecen During the Academic Year of 1927/28. Frigyes Verzár was Rector of the University of Debrecen in the academic year of 1927–28. This task was particularly demanding for various reasons. First, construction work on the central building of the University was still underway, second, because in August 1927 the Research Institute of Tihany was opened, and Verzár had to direct that Institute,too. The actually existing conditions of commuting between Debrecen and Tihany rendered the fulfilment of this double load particularly troublesome. In spite of all the difficulties, however, the work of the Rector yielded rich results, as listed in the report of Rector held in September 1928.